An Islamic Legal Review of the Practice of Buying and Selling Hair Clippings - Nurbaiti; Kurniawan; Ahmad Edi Saputra (Zabags International Journal of Islamic Studies, 2025)
This study examines the practice of buying and selling hair clippings conducted at Lidya Salon, Talang Babat Subdistrict, from the perspective of Islamic law. Emerging within the expanding beauty industry, the commodification of human hair for extensions raises legal and ethical questions under fiqh al-mu‛āmalāt. The primary objective is to analyze the transactional mechanisms and assess their conformity with Islamic commercial principles. Employing a qualitative single-case study design, the research combines in-depth interviews, direct observation, and document analysis with a review of contemporary fiqh literature and relevant fatwas. Findings indicate that transactions are carried out without written contracts or explicit consent from clients, and that the object traded human hair clippings poses legal concerns because it originates from the human body. From an Islamic-law perspective, the practice can be characterized as a doubtful transaction (al-mu‛āmalāt al-mashbūhah) due to elements of uncertainty and unmet requirements for a permissible object of sale. The study contributes to contemporary fiqh discourse by highlighting the need for improved Islamic-legal literacy among small beauty-business actors and for clearer religious guidance regarding the commercial use of human-derived materials in the beauty sector.